Analisis jalur penggunaan label gizi, konsumsi minuman kemasan, dan status gizi remaja di Kecamatan Pasirkaliki, Kota Bandung - Anggrahini, Sabrina Gani; Rosdiana, Delita Septia; Syihab, Syifa F; Insani, Hurry Mega (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Teenagers' high consumption of packaged drinks can trigger obesity, so they need to be able to identify nutritional content through the nutritional labels on the packaging. The use of nutritional labels is a form of nutrition education that can help teenagers make food choices as an effort to prevent obesity.Objectives: Analyzing the correlation of practice in nutrition labelling with the nutritional status of junior high school students in Bandung.Methods: This study used a quantitative descriptive design with cross-sectional methods. In October 2024, we conducted this study at public and private junior high schools in Pasirkaliki District, Bandung City, involving 60 students. This study employed a purposive sampling technique for selecting participants. The variables analyzed in this study include the practice of using nutrition labels, frequency of consumption of packaged drinks, and nutritional status. The research data were analyzed using univariate tests and multivariate tests using path analysis to see the correlatio between variables.Results: The results of the study indicated that there was a moderate correlation between the frequency of consumption of packaged drinks and nutritional status (p=0,020; b=0,405), the practice of using nutritional labels with the frequency of consumption of packaged drinks (p=0,003; b=0,470), and the practice of using nutritional labels with  nutritional status (p=0,023; b=0,383). Meanwhile, there was a weak correlation between the practice of using nutritional labels with nutritional status through the frequency of consumption of packaged drinks as an intervening variable (p=0,048; b=0,190).Conclusion: The study's results stated that the practice of using nutritional labels correlated with nutritional status, with the frequency of consumption of packaged drinks as an intervening variable.